Preparation and dielectric properties of the KBiScNbO6 double perovskite. Issue 2 (3rd December 2013) - Ivanov, Oleg; Danshina, Elena; Sudzhanskaya, Irina; Vasil'ev, Alexei
Abstract Ceramic KBiScNbO6 compound was synthesized for the first time. X‐ray diffraction analysis revealed that at room temperature the samples consist of a mixture of the perovskite and pyrochlore phases. The dominant phase is the perovskite one. This phase can be described as distorted pseudocubic Pm3m structure with unit‐cell parameter ac = 4.069 Å. Rhombohedral distortion leading the polar R3m phase is assumed to be one of possible structural distortions. Dielectric measurements of the compound under study demonstrated anomalies associated with relaxor ferroelectric behavior (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)